Pemberdayaan Masyarakat Kelurahan Air Hitam Kota Samarinda di Era New Normal - Husni Thamrin (LP3M STAI Darussalam Krempyang Nganjuk, 2021)
The community empowerment of Air Hitam Kelurahan, Kota Samarinda was carried out by the PkM team to open business opportunities, skills, innovation, and awareness of health protocols in community activities, especially in the new normal era. It is hoped that this service activity will provide direction to the community to create an atmosphere, condition or climate that allows the potential for the community to develop, especially during the Covid-19 pandemic. Based on this focus, the objectives of PkM are (1) Community empowerment through waste paper processing programs, especially for PKK mothers, (2) Improve health protocols for transportation services, and (3) Simultaneous Pilkada preparation in the New Normal Era. The method of implementation is through the Participatory Need Assessment (PNA) approach and also assistance in collaboration, idea contributors, facilitators with local communities. The result of this PkM is to hold a training program for making used newspaper crafts which aims to open business opportunities for housewives for members of the Air Hitam Village PKK, as well as to socialize the application of Health protocols in transportation services and the implementation of Pilkada to stay safe during the Covid-19 pandemic.